(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2023)
In the present work a novel polymer/metal oxide composites containing Polyvinyl Chloride (PVC) and Ag2O nanoparticles (NP) were fabricated under room and elevated temperatures. The PVC/Ag2O NC has been fabricated to enhance the electronic application such as memory devices, sensors, electronic luminescent devices and medical applications. The Ag2O NP was synthesized by dropwise mixing process having 25 nm in size with spherical surface morphology. The Fourier transform infrared spectroscopy (FTIR) was taken for (1) virgin PVC film (2) PVC/Ag2O NC and PVC/Ag2O (heat treated) Composites. The formation of absorbance peaks, their shifting, intensity and maximum absorbance values were considered in all the three C C, C-Cl and C-H classified stretching modes of vibrations for different composites. It was found in C-C stretch range the virgin PVC back bone chain occurs at 1101 cm-1 which shifted to 1076 cm-1 for PVC/Ag2O NC, further shift is evident for PVC/Ag2O (heat treated) Composites at 1151 cm-1. In addition rocking vibration and wagging of methylene group changes in the same fashion. The change in spectral feature takes places due to filling of Ag2O NP in PVC matrix, indicates that changes in dipole moments occur as a result of molecular vibrations. It is also observed the absorbance peaks value is high for virgin PVC film for all modes of stretching vibration, which decreases for Ag2O/PVC (NC) further decrease is evident for Ag2O/PVC (NC) heat treated composite.